2020
DOI: 10.3389/fnins.2020.579958
|View full text |Cite
|
Sign up to set email alerts
|

Serum Neurofilament Levels in Children With Febrile Seizures and in Controls

Abstract: Objective Neuroaxonal damage is reflected by serum neurofilament light chain (sNfL) values in a variety of acute and degenerative diseases of the brain. The aim of this study was to investigate the impact of febrile and epileptic seizures on sNfL, serum copeptin, and prolactin levels in children compared with children with febrile infections without convulsions. Methods A prospective cross-sectional study was performed in children aging 6 months to 5 years presenting wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…These increases accompany hippocampal atrophy in cognitively healthy older adults, which has suggested possible AD-independent, ageexpected hippocampal decline (Idland et al, 2017). However, younger children have higher serum NfL levels than older children reaching the lowest level between the age of 10 and 15 years, then increasing in a linear fashion until the age of 60 years and accelerating non-linearly afterward (Evers et al, 2020;Khalil et al, 2020;Reinert et al, 2020). There are various proposed bases for serum NfL elevation in aging, including subclinical senescence with greater neuronal apoptosis (Khalil et al, 2020) and increased disruption of blood-brain barrier (Sweeney et al, 2018).…”
Section: Neurofilament Light Chain Levels In Normal Individualsmentioning
confidence: 99%
“…These increases accompany hippocampal atrophy in cognitively healthy older adults, which has suggested possible AD-independent, ageexpected hippocampal decline (Idland et al, 2017). However, younger children have higher serum NfL levels than older children reaching the lowest level between the age of 10 and 15 years, then increasing in a linear fashion until the age of 60 years and accelerating non-linearly afterward (Evers et al, 2020;Khalil et al, 2020;Reinert et al, 2020). There are various proposed bases for serum NfL elevation in aging, including subclinical senescence with greater neuronal apoptosis (Khalil et al, 2020) and increased disruption of blood-brain barrier (Sweeney et al, 2018).…”
Section: Neurofilament Light Chain Levels In Normal Individualsmentioning
confidence: 99%
“…This observation is supported by a previous study which reported that serum NfL was not altered in children with febrile seizures. 12 However, it had also previously been reported that NfL may reflect the contribution of seizure status to CLN3 disease severity. 13 The lowest NfL levels in this cohort was in the atypical patient 667.…”
Section: Resultsmentioning
confidence: 94%
“…11,[13][14][15][16] Of note, there are few studies that also looked at NfL in epilepsy, and partial or generalized epileptic seizures were not associated with an increase in NfL levels but status epilepticus resulted in increased NfL. 17,18 Avoiding the increase in blood neurofilaments or decreasing their levels could be a relevant aspect for assessing the efficacy of forthcoming treatments-as shown in multiple sclerosis (MS) (Table 1). 19…”
Section: Cognitionmentioning
confidence: 99%
“…Thus, the second sample taken few days after the event will not show a change in NfL levels if the cognition was altered for example because of Alzheimer disease (AD), Parkinson disease (PD), or vascular dementia 11,13‐16 . Of note, there are few studies that also looked at NfL in epilepsy, and partial or generalized epileptic seizures were not associated with an increase in NfL levels but status epilepticus resulted in increased NfL 17,18 . Avoiding the increase in blood neurofilaments or decreasing their levels could be a relevant aspect for assessing the efficacy of forthcoming treatments—as shown in multiple sclerosis (MS) (Table 1).…”
Section: Cognition and Speechmentioning
confidence: 99%